El modernismo radical de Oscar Niemeyer - Philippou, Styliane (Revista Científica de Arquitectura y Urbanismo, 2013)
RESUMEN PALABRAS CLAVE The Radical Modernism of Oscar Niemeyer ABSTRACT : As the pre-eminent figure of one of the most innovative and irreverent national interpretations of architectural modernism, and radical critic of orthodox modernist aesthetic formulae and moralizing ideologies, Oscar Niemeyer (1907–2012) occupies a unique place in the history of architecture. Motivated by a post-colonial wish to undo the image of Brazil as backward, he privileged invention and tirelessly explored the structural and formal possibilities of reinforced concrete, striving for ‘splendour’ and ‘lightness’ – qualities in excess of the functionalist fulfilment of programmatic requirements. Transgressing doctrinaire Modernism and subverting hegemonic cultural models, Niemeyer’s work affirmed spectacle and luxury, pleasure, beauty and sensuality as legitimate architectural pursuits. His aesthetic of excess, habitually interpreted as a reflection of Brazil’s tropical Otherness, was rooted in the country’s native traditions and tropical landscape, and challenged the dominance of clean white walls, straight lines and right angles, which, for Niemeyer, ‘issued from a European ethical tradition’. KEYWORDS : Oscar Niemeyer, modernism, Brazil, antropofagia, irreverence, transgression of orthodox modernism, subversion of hegemonic cultural models, decolonization. : Oscar Niemeyer, modernismo, Brasil, antropofagia, irreverencia, transgresión de la ortodoxia modernista, subversión de modelos hegemónicos culturales, descolonización. : Oscar Niemeyer (1907–2012), el protagonista de una de las más innovadoras e irreverentes interpretaciones del modernismo arquitectónico y un crítico radical de las fórmulas estéticas e ideologías moralistas del modernismo ortodoxo, ocupa un lugar único en la historia de la arquitectura. Motivado por el deseo poscolonial de derribar la imagen de un Brasil atrasado, Niemeyer privilegió la invención y exploró incasablemente las posibilidades estructurales y formales del hormigón armado, buscando cualidades que exceden los requisitos programáticos del funcionalismo. Su arquitectura afirmó el espectáculo, el lujo, el placer, la belleza y la sensualidad como legítimos fines arquitectónicos, para transgredir el modernismo doctrinario y subvertir los modelos culturales hegemónicos. Su estética del exceso estaba arraigada en las tradiciones propias de Brasil y su paisaje tropical, y desafió el predominio de los muros blancos y puros, las líneas y los ángulos rectos, los cuales procedían, según Niemeyer, de una «tradición ética europea».